An atomizing assembly, a preparation method and application thereof

CN120713301BActive Publication Date: 2026-10-23ALD GRP
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410374296.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-03-29
Publication Date
2026-10-23
Estimated Expiration
2044-03-29

AI Technical Summary

Technical Problem

平面陶瓷可通过调节层与层之间的结构性能,进而制备出梯度多孔陶瓷的优势,但现有的梯度陶瓷用于电子雾化液的雾化时,由于气道不集中,烟雾需要从平面陶瓷的周边绕出来,再进入气道中传输至人体,导致气体传输效率低、口感不佳等问题;而热压铸工艺制备出的柱状陶瓷结构相对单一,很难形成具有梯度多孔结构的陶瓷基体

Benefits of technology

[0061]本发明的有益效果是:本发明雾化组件中的第一陶瓷层和第三陶瓷层具有较大的孔径和导热率,较大的孔径可以使电子雾化液快速通过并进入第二陶瓷层中,导液性能优异,避免第二陶瓷层发热体干烧或者雾化的气溶胶量太少,影响抽吸口感,同时较高的导热率可以将发热体干烧时产生的热量快速传导出去,减少干烧几率;第二陶瓷层具有较小的孔径和优异的储液性能,可以利用毛细管力将第一陶瓷层和第三陶瓷层中的电子雾化液快速吸附入第二陶瓷层中储存,避免发热体干烧,在发热体初始工作时即具有较高的雾化量,提高雾化效果和抽吸体验,第二陶瓷层具有较低的导热率,避免发热体的发热量被第二陶瓷层吸收太多,从而影响雾化效果,此外,通过设置中心气体通道和发热体粗糙度设计可以提升气溶胶的传输效率、口感体验及雾化组件的可加工性和使用寿命。本发明中的雾化组件可以根据使用需要,通过调整各层的制备原料进而调节孔径、孔隙率及导热率。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004766576990000111
    Figure BDA0004766576990000111
  • Figure BDA0004766576990000131
    Figure BDA0004766576990000131
  • Figure HDA0004766577000000011
    Figure HDA0004766577000000011
Patent Text Reader

Abstract

The present application relates to a kind of atomization components and its preparation method and application, the atomization component includes heating body and the first ceramic layer, second ceramic layer and third ceramic layer are sequentially stacked;The pore size of the first ceramic layer and third ceramic layer is all greater than second ceramic layer, the thermal conductivity of the first ceramic layer and third ceramic layer is all greater than second ceramic layer;Gas passage is provided in the second ceramic layer;The heating body includes oppositely arranged first surface and second surface;The first surface is in contact with second ceramic layer, and the second surface is towards gas passage;The roughness of the first surface is greater than second surface.The atomization component in the present application has excellent liquid guiding performance and liquid storage performance, can avoid heating body dry burning or too little aerosol amount of atomization, affect smoking taste, and at the same time, the first ceramic layer and third ceramic layer have higher thermal conductivity, can quickly conduct the heat generated when heating body dry burning, reduce the probability of dry burning.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of atomization, specifically relating to an atomization component, its preparation method, and its application. Background Technology

[0002] The atomizing coil is the core component of an e-cigarette. E-liquid is injected into the coil, and when heated, it atomizes into vapor. Therefore, the atomization effect of the atomizing coil determines the quality and taste of the vapor. Currently, e-cigarette atomizing coils are mainly composed of porous ceramic materials and heating elements. The porous ceramic materials are primarily columnar ceramics prepared by hot-pressing and planar ceramics prepared by dry pressing. Planar ceramics can achieve the advantage of gradient porous ceramics by adjusting the structural properties between layers. However, when existing gradient ceramics are used for atomizing e-liquid, the airflow is not concentrated, and the vapor needs to flow around the periphery of the planar ceramic before entering the airflow and being transported to the body, resulting in low gas transmission efficiency and poor taste. Meanwhile, the columnar ceramics prepared by hot-pressing have a relatively simple structure, making it difficult to form a ceramic matrix with a gradient porous structure. During the research process, the inventors discovered that the dry pressing method for preparing gradient hollow columnar porous ceramics is limited by structure and process, making it impossible to place the heating element in the inner wall of the air passage during a one-time molding process. This results in a complex preparation process, and the resulting gradient hollow columnar porous ceramics cannot meet the high-efficiency transmission requirements of high-viscosity electronic atomizing liquids. Summary of the Invention

[0003] In order to overcome the problems existing in the prior art, one of the objectives of the present invention is to provide an atomizing component.

[0004] The second objective of this invention is to provide a method for preparing an atomizing component.

[0005] The third objective of this invention is to provide an electronic atomization device.

[0006] The fourth objective of this invention is to provide an application of an atomizing component in the field of electronic atomization.

[0007] To achieve the above objectives, the technical solution adopted by the present invention is as follows:

[0008] A first aspect of the present invention provides an atomizing component, comprising a heating element and a first ceramic layer, a second ceramic layer, and a third ceramic layer stacked sequentially; the pore sizes of the first and third ceramic layers are both larger than those of the second ceramic layer, and the thermal conductivity of the first and third ceramic layers is both greater than that of the second ceramic layer; a gas channel is provided in the second ceramic layer; the heating element includes a first surface and a second surface disposed opposite to each other; the first surface is in contact with the second ceramic layer, and the second surface faces the gas channel; the roughness of the first surface is greater than that of the second surface.

[0009] In this invention, the first and third ceramic layers have larger pore sizes and higher thermal conductivity than the second ceramic layer. The larger pore size improves the liquid conduction rate of the porous ceramic, allowing high-viscosity liquids to quickly pass through the first and third ceramic layers and be introduced into and fill the second ceramic layer. Simultaneously, the higher thermal conductivity allows for rapid heat dissipation from the second ceramic layer, preventing overheating of the second ceramic layer and the heating element. The second ceramic layer has smaller pore sizes and lower thermal conductivity. The smaller pore size allows for strong capillary adsorption, enabling the high-viscosity liquid to be drawn into and stored within the porous structure of the second ceramic layer. Therefore, this special structural design allows the atomizing component to possess both excellent liquid conduction and storage properties. The roughness of the first and second surfaces on the heating element is different, with the first surface having a greater roughness than the second surface. This results in a greater interlocking force between the heating element and the second ceramic layer than between the heating element and the metal mold, making the atomizing component easier to process, resulting in higher product yield and a longer service life.

[0010] Preferably, the second ceramic layer has a gas channel penetrating through it; more preferably, the axis of the second ceramic layer has a gas channel penetrating through it. With this structure, when the heating element heats up, it rapidly atomizes the electronic atomizing liquid stored in the second ceramic layer into an aerosol. The aerosol is directly exported from the gas channel, resulting in a more concentrated aerosol, higher transmission efficiency, and better taste.

[0011] Preferably, the first ceramic layer and the third ceramic layer have the same material, preparation raw materials, pore size and thermal conductivity.

[0012] Preferably, the pore sizes of the first ceramic layer and the third ceramic layer are 11–20 μm, respectively.

[0013] Preferably, the thermal conductivity of the first ceramic layer and the third ceramic layer is 0.6 to 1.2 W / m·K, respectively.

[0014] Preferably, the thicknesses of the first ceramic layer and the third ceramic layer are 0.8 to 1.2 mm, respectively.

[0015] Preferably, the porosity of the first ceramic layer and the third ceramic layer is 53-60%, respectively.

[0016] Preferably, the materials of the first ceramic layer and the third ceramic layer are selected from at least one of alumina ceramics, silicon carbide ceramics, silicon nitride ceramics, and aluminum nitride ceramics.

[0017] Preferably, by mass percentage, the raw materials for preparing the first ceramic layer and the third ceramic layer respectively include 45-70% ceramic powder A, 15-30% pore-forming agent, and 15-25% sintering aid.

[0018] Preferably, the ceramic powder A is selected from at least one of alumina powder, silicon carbide powder, silicon nitride powder, and aluminum nitride powder.

[0019] Preferably, in the raw materials for preparing the first ceramic layer and the third ceramic layer, the pore-forming agent is selected from at least one of polystyrene microspheres, carbonates, carbon powder, flour, and sawdust.

[0020] Preferably, the particle size of the pore-forming agent in the raw materials for preparing the first and third ceramic layers is 25–70 μm.

[0021] Preferably, the sintering aid in the raw materials for preparing the first ceramic layer and the third ceramic layer is glass powder; more preferably, the glass powder is low-temperature glass powder that does not contain heavy metals.

[0022] Preferably, the pore size of the second ceramic layer is 4μm to 10μm.

[0023] Preferably, the thermal conductivity of the second ceramic layer is 0.3–0.6 W / m·K. When the thermal conductivity of the second ceramic layer is 0.6 W / m·K, the thermal conductivity of the first and third ceramic layers must be greater than 0.6 W / m·K. As a preferred embodiment, the thermal conductivity of the second ceramic layer is less than 0.6 W / m·K.

[0024] Preferably, the thickness of the second ceramic layer is 3 to 5 mm.

[0025] Preferably, the porosity of the second ceramic layer is 45-52%.

[0026] Preferably, the material of the second ceramic layer is selected from at least one of silicon oxide ceramics, alumina ceramics, cordierite ceramics, and silicon nitride ceramics.

[0027] Preferably, the second ceramic layer comprises the following raw materials by mass percentage: 35-60% ceramic powder B, 15-30% pore-forming agent, 17-35% sintering aid, 0.8%-1.5% release agent A, and 7%-10% green body reinforcing agent A.

[0028] Preferably, the ceramic powder B is selected from at least one of silicon oxide powder, alumina powder, cordierite powder, and silicon nitride powder.

[0029] Preferably, in the raw materials for preparing the second ceramic layer, the release agent A is selected from at least one of synthetic paraffin wax, microcrystalline wax, polyethylene wax, talc, mica, clay, and white clay.

[0030] Preferably, in the raw materials for preparing the second ceramic layer, the green body reinforcing agent A is selected from at least one of modified starch, methylcellulose, polyvinyl alcohol, propylene polymer, sodium alginate, dextrin, tannin, and sodium polyacrylate composite agent.

[0031] Preferably, the sintering aid in the raw materials for preparing the second ceramic layer is glass powder; more preferably, the glass powder is low-temperature glass powder that does not contain heavy metals.

[0032] Preferably, in the raw materials for preparing the second ceramic powder, the pore-forming agent is selected from at least one of polymethyl methacrylate, polystyrene microspheres, carbonates, carbon powder, and flour.

[0033] Preferably, in the raw materials for preparing the second ceramic powder, the particle size of the pore-forming agent is 10-20 μm.

[0034] Preferably, the raw materials for preparing the second ceramic layer contain mold release agent A and green body reinforcing agent A; the raw materials for preparing the first ceramic layer and the third ceramic layer contain mold release agent B and green body reinforcing agent B, respectively; the mass ratio of mold release agent A to mold release agent B is (1.2~1.7):1; the mass ratio of green body reinforcing agent A to green body reinforcing agent B is (1.2~1.7):1.

[0035] Preferably, in the raw materials for preparing the first ceramic layer and the third ceramic layer, the release agent B is selected from at least one of synthetic paraffin wax, microcrystalline wax, polyethylene wax, talc, mica, clay, and white clay.

[0036] Preferably, in the raw materials for preparing the first ceramic layer and the third ceramic layer, the green body reinforcing agent B is selected from at least one of modified starch, methylcellulose, polyvinyl alcohol, propylene polymer, sodium alginate, dextrin, tannin, and sodium polyacrylate composite agent.

[0037] Preferably, the roughness Ra value of the first surface is greater than 1 μm and the Rz value is greater than 5 μm; the roughness Ra value of the second surface is less than 0.2 μm and the Rz value is less than 1.4 μm.

[0038] The second aspect of the present invention provides a method for preparing the atomizing component provided in the first aspect of the present invention, comprising the following steps:

[0039] S1: Spread the raw materials for preparing the first ceramic layer evenly;

[0040] S2: Spread part of the preparation material for the second ceramic layer on the surface of the preparation material for the first ceramic layer, place a metal mold with a heating element in it, and then spread the remaining preparation material for the second ceramic layer.

[0041] S3: The raw material for preparing the third ceramic layer is laid flat on the surface of the raw material for preparing the second ceramic layer, and then pressed to obtain a ceramic green body;

[0042] S4: The ceramic green body is dried and demolded, and then calcined to obtain the atomizing component.

[0043] Preferably, the pressing step in step S3 is performed using a dry pressing method.

[0044] Preferably, the pressing pressure is 50-60 MPa.

[0045] Preferably, the pressing time is 5 to 10 minutes.

[0046] Preferably, the diameter of the metal mold is 1.5 to 2.8 mm and the height is 5 to 9 mm.

[0047] Preferably, the draft angle α of the metal mold is not higher than 5°, which is more conducive to demolding later.

[0048] Preferably, the drying temperature is 70–130°C.

[0049] Preferably, the drying time is 5 to 60 minutes.

[0050] Preferably, step S4 is: drying the ceramic green body once, then demolding it, drying it a second time, and then calcining it to obtain the atomizing component.

[0051] Preferably, the primary drying temperature is 70–90°C.

[0052] Preferably, the drying time is 15-30 minutes. Since the thermal conductivity of the metal mold is much higher than that of the porous ceramic green body, the second ceramic layer in the porous ceramic green body surrounding the metal mold will be preheated first. After being subjected to a certain amount of heat, the green body reinforcing agent A and the mold release agent A in the second ceramic layer can be better dispersed in the porous ceramic green body, which increases the viscosity, elasticity and strength of the inner wall of the porous ceramic green body to a certain extent. On the one hand, this is conducive to the heating element being more firmly embedded in the porous ceramic green body, and on the other hand, it is also more conducive to the metal mold being removed from the porous ceramic green body.

[0053] Preferably, the secondary drying temperature is 100–130°C.

[0054] Preferably, the secondary drying time is 5 to 30 minutes.

[0055] Preferably, the calcination temperature is 700–800°C.

[0056] Preferably, step S4 is as follows: the ceramic green body is dried at 70-90°C for 15-30 minutes, then demolded with a draft angle of no more than 5°, dried again at 100-130°C for 5-30 minutes, and then calcined at 700-800°C to obtain the product.

[0057] Preferably, step S4 is as follows: the ceramic green body is dried at 70-90°C for 15-30 minutes, then demolded with a draft angle of no more than 5°, and then calcined at 700-800°C to obtain the product.

[0058] A third aspect of the present invention provides an electronic atomizing device, including the atomizing component provided in the first aspect of the present invention.

[0059] Preferably, the electronic atomizing device includes an electronic cigarette.

[0060] The fourth aspect of the present invention provides the application of the atomizing component provided in the first aspect of the present invention in the field of electronic atomization.

[0061] The beneficial effects of this invention are as follows: The first and third ceramic layers in the atomizing component of this invention have large pore sizes and high thermal conductivity. The large pore size allows the electronic atomizing liquid to pass through quickly and enter the second ceramic layer, resulting in excellent liquid conduction performance. This prevents the heating element in the second ceramic layer from burning dry or the amount of atomized aerosol from being too small, which would affect the vaping experience. At the same time, the high thermal conductivity can quickly conduct away the heat generated when the heating element burns dry, reducing the chance of dry burning. The second ceramic layer has small pore sizes and excellent liquid storage performance. It can use capillary force to quickly adsorb the electronic atomizing liquid in the first and third ceramic layers into the second ceramic layer for storage, preventing the heating element from burning dry. It has a high atomization volume from the initial operation of the heating element, improving the atomization effect and vaping experience. The second ceramic layer has low thermal conductivity, preventing too much heat from the heating element from being absorbed by the second ceramic layer, which would affect the atomization effect. In addition, by setting a central gas channel and designing the roughness of the heating element, the aerosol transmission efficiency, vaping experience, processability, and service life of the atomizing component can be improved. The atomizing component in this invention can adjust the pore size, porosity, and thermal conductivity by adjusting the raw materials used in the preparation of each layer, according to the needs of use.

[0062] The atomizing component preparation method of this invention adopts a dry pressing process combined with a preheating process, which solves the problem of difficult demolding. A gas channel for aerosol circulation is prepared in the second ceramic layer. Moreover, the preparation method of this invention has mild conditions, low cost, and is easy to operate. It can be applied to mass production, with stable process and high product yield. Attached Figure Description

[0063] Figure 1 This is a schematic diagram of the atomizing component in an embodiment of the present invention.

[0064] Figure 2 This is a schematic diagram of the fabrication process of the atomizing component in Example 1.

[0065] Figure 3 This is a schematic diagram of the draft angle in an embodiment of the present invention. Detailed Implementation

[0066] To facilitate understanding of the present invention, a more complete description will be given below with reference to the accompanying drawings. Preferred embodiments of the invention are shown in the drawings. However, the invention can be implemented in many different forms and is not limited to the embodiments described herein. Rather, these embodiments are provided to provide a thorough and complete understanding of the disclosure of the invention.

[0067] Reference Figure 1 The schematic diagram of the atomizing component is shown in some embodiments of the present invention. The present invention provides an atomizing component including a heating element and a first ceramic layer, a second ceramic layer, and a third ceramic layer stacked sequentially. The pore sizes of the first and third ceramic layers are both larger than those of the second ceramic layer, and the thermal conductivity of the first and third ceramic layers is also greater than that of the second ceramic layer. A gas channel is provided in the second ceramic layer. The heating element includes a first surface and a second surface disposed opposite to each other. The first surface is in contact with the second ceramic layer, and the second surface faces the gas channel. The roughness of the first surface is greater than that of the second surface. In this invention, the first and third ceramic layers have larger pore sizes and higher thermal conductivity than the second ceramic layer. This improves the liquid conduction rate, allowing high-viscosity liquids to quickly pass through the first and third ceramic layers and be introduced and stored in the second ceramic layer. Simultaneously, the high thermal conductivity also allows for rapid heat dissipation from the second ceramic layer, preventing overheating of the second ceramic layer and the heating element, reducing the dry-burning temperature of the heating element, and preventing reduced lifespan of the atomizing component due to dry burning. The second ceramic layer has smaller pore sizes and lower thermal conductivity, allowing for strong capillary adsorption to store high-viscosity liquids within its porous structure. This results in a larger liquid storage capacity within the second ceramic layer, reducing the possibility of dry burning. Furthermore, the lower thermal conductivity prevents excessive heat loss from the heating element, which could lead to poor atomization. Therefore, this unique structural design enables the atomizing component to possess both excellent liquid conduction and storage properties.

[0068] In some embodiments of the present invention, a gas channel penetrating the second ceramic layer is provided; in some embodiments, a gas channel penetrating the second ceramic layer is provided along the axis of the second ceramic layer; in some specific embodiments, the gas channel can be cylindrical, quasi-cylindrical, conical, quasi-conical, cubic prism, etc. When the heating element heats up, it atomizes the electronic atomizing liquid stored in the second ceramic layer into an aerosol. The aerosol is directly exported from the gas channel, resulting in a more concentrated aerosol, higher transmission efficiency, and better taste.

[0069] In some embodiments of the present invention, the diameter of the gas channel is 1.5 to 2.8 mm.

[0070] In some embodiments of the present invention, the first ceramic layer and the third ceramic layer have the same material, preparation raw materials, pore size and thermal conductivity.

[0071] In some embodiments of the present invention, the pore sizes of the first ceramic layer and the third ceramic layer are 11 to 20 μm, respectively.

[0072] In some embodiments of the present invention, the thermal conductivity of the first ceramic layer and the third ceramic layer is 0.6–1.2 W / m·K, respectively. When the pore size of the first ceramic layer and the third ceramic layer is 11–20 μm and the thermal conductivity is 0.6–1.2 W / m·K, high-viscosity liquids can be rapidly conducted from the first ceramic layer or the third ceramic layer to the second ceramic layer, thereby improving the liquid transport efficiency.

[0073] In some embodiments of the present invention, the thicknesses of the first ceramic layer and the third ceramic layer are 0.8 to 1.2 mm, respectively.

[0074] In some embodiments of the present invention, the materials of the first ceramic layer and the third ceramic layer are selected from at least one of alumina ceramic, silicon carbide ceramic, silicon nitride ceramic, and aluminum nitride ceramic.

[0075] In some embodiments of the present invention, the raw materials for preparing the first ceramic layer and the third ceramic layer, by mass percentage, respectively include 45-70% ceramic powder A, 15-30% pore-forming agent, and 15-25% sintering aid.

[0076] In some embodiments of the present invention, ceramic powder A is selected from at least one of alumina powder, silicon carbide powder, silicon nitride powder, and aluminum nitride powder.

[0077] In some embodiments of the present invention, the pore-forming agent in the raw materials for preparing the first ceramic layer and the third ceramic layer is selected from at least one of polystyrene microspheres, carbonates, carbon powder, flour, and sawdust.

[0078] In some embodiments of the present invention, the particle size of the pore-forming agent in the raw materials for preparing the first ceramic layer and the third ceramic layer is 25-70 μm.

[0079] In some embodiments of the present invention, the sintering aid in the preparation of the first ceramic layer and the third ceramic layer is glass powder. In some embodiments, the glass powder is low-temperature glass powder that does not contain heavy metals.

[0080] In some embodiments of the present invention, the pore size of the second ceramic layer is 4 μm to 10 μm. The smaller pore size is beneficial for using capillary adsorption to adsorb and store the liquid in the first and third ceramic layers in the second ceramic layer. The special structure of the second ceramic layer can provide the necessary oil film layer for the heating element, that is, the second ceramic layer has a good liquid storage capacity. The electronic atomizing liquid is stored in the second ceramic layer, which can still ensure that there is a lot of aerosol in the initial stage of operation of the atomizing component, effectively avoiding the phenomenon that there is no aerosol or very little aerosol in the first suction.

[0081] In some embodiments of the present invention, the thermal conductivity of the second ceramic layer is 0.3–0.6 W / m·K. This low thermal conductivity prevents excessive heat absorption by the porous ceramic layer from the heating element, thus avoiding insufficient heat generation and a small amount of atomized aerosol.

[0082] In some embodiments of the present invention, the thickness of the second ceramic layer is 3 to 5 mm.

[0083] In some embodiments of the present invention, the material of the second ceramic layer is selected from at least one of silicon oxide ceramics, alumina ceramics, cordierite ceramics, and silicon nitride ceramics.

[0084] In some embodiments of the present invention, the second ceramic layer comprises the following raw materials by mass percentage: 35-60% ceramic powder B, 15-30% pore-forming agent, 17-35% sintering aid, 0.8%-1.5% release agent A, and 7%-10% green body reinforcing agent A. Because the second ceramic layer needs to bond with the heating element and also needs to detach from the metal mold, a certain amount of release agent A and green body reinforcing agent A needs to be added to the raw materials for preparing the second ceramic layer. The amount of release agent A and green body reinforcing agent A needs to be greater than that of the first and third ceramic layers. However, the difference between the amount of release agent A and green body reinforcing agent A in the second ceramic layer and that in the first and third ceramic layers cannot be too large; otherwise, defects will exist at the bonding interface between the first / third ceramic layer and the second ceramic layer, resulting in a decrease in the performance of the porous ceramic.

[0085] In some embodiments of the present invention, ceramic powder B is selected from at least one of silicon oxide powder, alumina powder, cordierite powder, and silicon nitride powder.

[0086] In some embodiments of the present invention, the release agent A in the raw materials for preparing the second ceramic layer is selected from at least one of synthetic paraffin wax, microcrystalline wax, polyethylene wax, talc, mica, clay, and white clay. The function of the release agent A is to allow the metal mold to be easily removed from the porous ceramic body.

[0087] In some embodiments of the present invention, the green body reinforcing agent A in the raw materials for preparing the second ceramic layer is selected from at least one of modified starch, methylcellulose, polyvinyl alcohol, propylene polymer, sodium alginate, dextrin, tannin, and sodium polyacrylate composite. The function of the green body reinforcing agent A is to ensure that the porous ceramic green body has high strength and is not easily damaged during demolding.

[0088] In some embodiments of the present invention, the sintering aid in the preparation of the second ceramic layer is glass powder. In some embodiments, the glass powder is low-temperature glass powder that does not contain heavy metals.

[0089] In some embodiments of the present invention, the pore-forming agent in the raw materials for preparing the second ceramic powder is selected from at least one of polymethyl methacrylate, polystyrene microspheres, carbonates, carbon powder, and flour. In some embodiments, the particle size of the pore-forming agent in the raw materials for preparing the second ceramic powder is 10–20 μm.

[0090] In some embodiments of the present invention, the raw materials for preparing the second ceramic layer contain mold release agent A and green body reinforcing agent A; the raw materials for preparing the first ceramic layer and the third ceramic layer contain mold release agent B and green body reinforcing agent B, respectively; the mass ratio of mold release agent A to mold release agent B is (1.2~1.7):1; the mass ratio of green body reinforcing agent A to green body reinforcing agent B is (1.2~1.7):1.

[0091] In some embodiments of the present invention, the release agent B in the raw materials for preparing the first ceramic layer and the third ceramic layer is selected from at least one of synthetic paraffin wax, microcrystalline wax, polyethylene wax, talc, mica, clay, and white clay.

[0092] In some embodiments of the present invention, the green body reinforcing agent B in the raw materials for preparing the first ceramic layer and the third ceramic layer is selected from at least one of modified starch, methylcellulose, polyvinyl alcohol, propylene polymer, sodium alginate, dextrin, tannin, and sodium polyacrylate composite agent.

[0093] In some embodiments of the present invention, the heating element can be in the shape of a wire, a sheet, or a combination of multiple wires, and can fit well onto the outer surface of the metal mold. After demolding, the metal mold is removed, and the heating element is embedded in the inner wall of the second ceramic layer near the gas channel.

[0094] In some embodiments of the present invention, the roughness Ra value of the first surface is greater than 1 μm, and the Rz value is greater than 5 μm; the roughness Ra value of the second surface is less than 0.2 μm, and the Rz value is less than 1.4 μm. The roughness of the heating element surface can be obtained by methods such as polishing with polishing paper, etching, or mold imprinting. The uneven structure of the first surface is more conducive to achieving interlocking and bonding with the porous ceramic raw material, while the smooth surface of the second surface is more conducive to reducing friction with the metal mold surface and facilitating removal from the metal mold.

[0095] In some embodiments of the present invention, the present invention also provides a method for preparing an atomizing component, comprising the following steps:

[0096] S1: Spread the raw materials for preparing the first ceramic layer evenly;

[0097] S2: Spread part of the preparation material for the second ceramic layer on the surface of the preparation material for the first ceramic layer, place a metal mold with a heating element in it, and then spread the remaining preparation material for the second ceramic layer.

[0098] S3: The raw material for preparing the third ceramic layer is laid flat on the surface of the raw material for preparing the second ceramic layer, and then pressed to obtain a ceramic green body;

[0099] S4: Dry and demold the ceramic green body, then calcine it to obtain the atomizing component.

[0100] In some embodiments of the present invention, the mass ratio of a portion of the raw materials to the remaining raw materials is 1:1, thereby positioning the metal mold with the heating element at the axis of the second ceramic layer.

[0101] In some embodiments of the present invention, the metal mold is a cylindrical metal mold or a near-cylindrical metal mold, wherein a near-cylindrical metal mold refers to a metal mold with slightly different diameters at both ends. In some embodiments, a heating element is provided on the metal mold; in some embodiments, a metal heating wire is wound around the surface of the metal mold. In some embodiments, a second ceramic layer extends from at least one end of the metal mold.

[0102] In some embodiments of the present invention, the diameter of the metal mold is 1.5 to 2.8 mm and the height is 5 to 9 mm.

[0103] In some embodiments of the present invention, the draft angle α of the metal mold is no higher than 5°, which is more conducive to subsequent demolding. The larger the draft angle, the more difficult the demolding. (Refer to...) Figure 3 The structural diagram shows that, in this invention, draft angle refers to the draft angle, which is a slope designed to facilitate the removal of the mold.

[0104] In some embodiments of the present invention, step S4 involves drying the ceramic green body once, then removing the mold for a second drying, and then calcining it to obtain the atomizing component.

[0105] In some embodiments of the present invention, the primary drying temperature is 70–90°C.

[0106] In some embodiments of the present invention, the drying time is 15–30 minutes. Since the thermal conductivity of the metal mold is much higher than that of the second ceramic layer, the second ceramic layer surrounding the metal mold is preheated. After being heated, the green body reinforcing agent A and the release agent A in the second ceramic layer can be better dispersed in the porous ceramic green body, increasing the viscosity, elasticity, and strength of the inner wall of the porous ceramic green body to a certain extent. This facilitates the more firmly the heating element is embedded in the porous ceramic green body and also makes it easier to remove the metal mold from the porous ceramic green body. Excessive drying temperature and time will lead to excessive moisture loss from the porous ceramic powder, resulting in excessive volume shrinkage and difficulty in demolding.

[0107] In some embodiments of the present invention, the secondary drying temperature is 100–130°C.

[0108] In some embodiments of the present invention, the secondary drying time is 5 to 30 minutes.

[0109] In some embodiments of the present invention, the calcination temperature is 700–800°C.

[0110] In some embodiments of the present invention, step S4 is as follows: the ceramic green body is dried once at 70-90°C for 15-30 minutes, then demolded with a draft angle of no more than 5°, then dried again at 100-130°C for 5-30 minutes, and then calcined at 700-800°C to obtain the product.

[0111] In some embodiments of the present invention, step S4 is: drying the ceramic green body at 70-90°C for 15-30 minutes, then demolding it with a draft angle of no more than 5°, and then firing it at 700-800°C to obtain the product.

[0112] In some embodiments of the present invention, the present invention also provides an electronic atomizing device, including the atomizing components provided in the above embodiments.

[0113] In some embodiments of the present invention, the present invention provides the application of the atomizing components provided in the above embodiments in the field of electronic atomization.

[0114] The present invention will be further described in detail below with reference to specific embodiments, but the implementation and protection of the present invention are not limited thereto.

[0115] Example 1

[0116] Reference Figure 2 As shown, this example provides an atomizing component composed of a first ceramic layer, a second ceramic layer, and a third ceramic layer stacked sequentially. The second ceramic layer has a hollow cylindrical gas channel at its axis, and a heating wire is embedded in the inner wall of the gas channel. The pore sizes of the first and third ceramic layers are both larger than those of the second ceramic layer, and the thermal conductivity of both the first and third ceramic layers is greater than that of the second ceramic layer. The heating element has a first surface and a second surface arranged opposite to each other; the first surface is in contact with the second ceramic layer, and the second surface faces the gas channel; the roughness of the first surface is greater than that of the second surface.

[0117] The atomizing component in this example was prepared using the following method, with the specific steps as follows:

[0118] (1) Preparation of raw materials for the first, second, and third ceramic layers:

[0119] Weigh out 50% alumina, 25% glass powder, and 25% polystyrene microspheres by mass percentage, wherein the polystyrene microspheres have a particle size of 35 μm. After low-speed ball milling and thorough mixing, they are prepared into raw materials for the preparation of the first ceramic layer and the third ceramic layer, respectively.

[0120] Weigh out 50% silicon dioxide, 22.2% glass powder, 22% polystyrene microspheres, 0.8% microcrystalline wax, and 5% methylcellulose by mass percentage, wherein the polystyrene microspheres have a particle size of 15μm. After low-speed ball milling and thorough mixing, the raw materials for preparing the second ceramic layer are prepared.

[0121] (2) Preparation of porous ceramic green body

[0122] The raw material for preparing the first ceramic layer is evenly spread on the first layer of the mold, with a thickness of 1.2 mm. Then, half of the raw material for preparing the second ceramic layer is evenly spread on the raw material for preparing the first ceramic layer, with a thickness of 1.2 mm. A metal cylindrical mold (with diameters of 2 mm and 2.4 mm at both ends, respectively) with heating wires on the outside (the inner surface of the heating wires is polished with polishing paper to create a first surface with a certain roughness, Ra = 4 μm, Rz = 9 μm; the second surface is as smooth as possible, Ra = 0.15 μm, Rz = 0.6 μm) is placed on the raw material for preparing the second ceramic layer. It is gently pressed until half of the volume of the metal cylindrical mold is embedded in the raw material for preparing the second ceramic layer. Then, the remaining half of the raw material for preparing the second ceramic layer is spread evenly on the metal cylindrical mold and the previously prepared raw material for preparing the second ceramic layer, completing the application of the raw material for preparing the second ceramic layer. This ensures that the metal cylindrical mold with the heating wires is completely enclosed within the raw material for preparing the second ceramic layer. Finally, the raw materials for preparing the third ceramic layer are spread on top of the raw materials for preparing the second ceramic layer, and dry pressing is used to form the ceramic green body at a pressure of 52 MPa and a holding time of 6 min. The green body is then removed to obtain the ceramic green body.

[0123] (3) Preparation of atomizing components

[0124] The ceramic green body was dried in an 80°C drying oven for 30 minutes. After cooling, a small cylindrical metal strip was aligned with the end of a 2mm section of a cylindrical metal mold and gently pushed out of the mold (draft angle 4°). The mold was then removed and set aside, ensuring that the heating wire remained inside the cylindrical air channel of the ceramic green body. The ceramic green body was then dried in a 100°C drying oven for 3 hours. It was then heated to 750°C in a programmable temperature controlled furnace at a rate of 5°C / min and held at that temperature for 1.5 hours. The furnace was then cooled to room temperature to obtain the atomizing component used in this example.

[0125] The porosity, pore size, thermal conductivity, and compressive strength of the first, second, and third ceramic layers in Example 1 were tested respectively, and the specific test results are recorded in Table 1 below.

[0126] Table 1. Test results of porosity, pore size, thermal conductivity, and compressive strength.

[0127]

[0128] As shown in Table 1, the first and third ceramic layers prepared in Example 1 have the same porosity, pore size, thermal conductivity, and compressive strength. The porosity, pore size, and thermal conductivity of the first ceramic layer are all higher than those of the second ceramic layer, while the compressive strength is lower. This allows the atomizing component in Example 1 to have the following properties: when the electronic atomizing liquid is supplied from the first and third ceramic layers, it can quickly pass through the first and third ceramic layers and enter the second ceramic layer, resulting in a higher liquid transport rate. The second ceramic layer has a smaller pore size, resulting in better liquid storage performance. When the heating wire atomizes the electronic atomizing liquid, it can achieve a higher concentration of aerosol in the initial atomization stage, improving the vaping experience and preventing the heating wire from burning out.

[0129] Example 2

[0130] The difference between the preparation method of the atomizing component in this example and that in Example 1 is:

[0131] (1) The raw materials for the preparation of the first ceramic layer and the third ceramic layer by mass percentage are as follows: 43% alumina, 28.4% glass powder, 23.5% polystyrene microspheres, 0.6% microcrystalline wax, and 4.5% sodium polyacrylate.

[0132] (2) The raw materials for the preparation of the second ceramic layer are as follows by mass percentage: 50% silicon dioxide, 22.3% glass powder, 20% polystyrene microspheres, 0.9% microcrystalline wax, and 6.8% sodium polyacrylate.

[0133] (3) The metal cylindrical mold is a metal cylindrical mold with different diameters at both ends. One end has a diameter of 2mm and the other end has a diameter of 2.4mm. The draft angle of the metal cylindrical mold is 4°.

[0134] (4) The inner surface of the heating wire is polished with polishing paper to form a first surface with a certain roughness (Ra=3μm, Rz=7μm), and the second surface is as smooth as possible (Ra=0.1μm, Rz=0.7μm).

[0135] (5) First, keep the ceramic green body at 80℃ for 20 minutes, then take out the metal column mold, then keep it at 120℃ for 10 minutes, and then calcine it.

[0136] Example 3

[0137] The difference between the preparation method of the atomizing component in this example and that in Example 1 is:

[0138] (1) The raw materials for the preparation of the first ceramic layer and the third ceramic layer by mass percentage are as follows: 47% alumina, 23% glass powder, 24.2% polystyrene microspheres, 0.8% paraffin wax, and 5% methylcellulose;

[0139] (2) The raw materials for the preparation of the second ceramic layer are as follows by mass percentage: 50% silicon dioxide, 21% glass powder, 22% polystyrene microspheres, 1% paraffin wax, and 6% methylcellulose.

[0140] (3) The metal cylindrical mold is a metal cylindrical mold with different diameters at both ends. One end has a diameter of 2mm and the other end has a diameter of 2.3mm. The draft angle of the metal cylindrical mold is 3°.

[0141] (4) The first surface of the heating wire has Ra = 3μm and Rz = 7μm; the second surface has Ra = 0.1μm and Rz = 0.8μm.

[0142] (5) Keep the ceramic green body at 80℃ for 30 minutes, remove the metal column mold, and then calcine it.

[0143] Example 4

[0144] The difference between the preparation method of the atomizing component in this example and that in Example 3 is that both the first and second surfaces of the heating element are rough, with Ra = 5 μm and Rz = 10 μm on the first surface and Ra = 0.12 μm and Rz = 1.2 μm on the second surface.

[0145] The structures of the atomizing components in Examples 2 to 4 are all the same as those in Example 1.

[0146] Comparative Example 1

[0147] The difference between the preparation method of the atomizing component in this example and that in Example 1 is:

[0148] (1) The raw materials for the preparation of the first ceramic layer and the third ceramic layer by mass percentage are as follows: 48% alumina, 19.1% glass powder, 25% polystyrene microspheres (particle size 20μm), 0.9% paraffin, and 7% methylcellulose.

[0149] (2) The raw materials for the preparation of the second ceramic layer are as follows by mass percentage: 50% silicon dioxide, 22.2% glass powder, 22% polystyrene microspheres (particle size 20μm), 0.4% paraffin wax, and 2% methylcellulose.

[0150] (3) The metal cylindrical mold is a metal cylindrical mold with the same diameter at both ends, which is 2mm (i.e., the draft angle is 0°).

[0151] (4) The outer surface of the heating wire has different textures. The first surface is smooth, and the second surface has a Ra value of 3μm and an Rz value of 7μm.

[0152] (5) Keep the ceramic green body at 120℃ for 30 minutes, remove the metal column mold, and then calcine it.

[0153] Comparative Example 2

[0154] The difference between the preparation method of the atomizing component in this example and that in Example 1 is that the first and second surfaces of the heating element in this example are both smooth.

[0155] The porosity, pore size, thermal conductivity, and compressive strength of the first, second, and third ceramic layers of the atomizing components in Examples 1-4 and Comparative Examples 1-2 were tested respectively, and the specific test results are recorded in Table 2 below.

[0156] Table 2. Results of ceramic performance and sample suction test.

[0157]

[0158] As shown in the table above, the average atomization amount of the atomizing components in Examples 1-4 is greater than that in Comparative Examples 1-2, and the dry-burning temperature is significantly lower than that in Comparative Examples 1-2. This further indicates that the first and third ceramic layers of the atomizing components in this invention have excellent liquid conductivity, which can quickly deliver the electronic atomized liquid to the second ceramic layer, avoiding dry burning of the heating element in the second ceramic layer or insufficient atomized aerosol, thus affecting the vaping experience. At the same time, the high thermal conductivity can quickly conduct away the heat generated when the heating element is dry-burning, reducing the dry-burning temperature. The second ceramic layer has a small pore size, which can use capillary force to quickly adsorb the electronic atomized liquid in the first and third ceramic layers into the second ceramic layer, and can store the electronic atomized liquid in the second ceramic layer, avoiding dry burning of the heating element. It can also have a high atomization amount when the heating element is initially working, improving the atomization effect and vaping experience. The second ceramic layer has a low thermal conductivity, preventing excessive heat absorption by the heating element, which would affect the atomization effect. Furthermore, the gas channel design improves the transmission efficiency, lifespan, and flavor experience of the atomized gas. Comparing data from Example 1 and Comparative Example 2 reveals that the roughness of the heating element affects the amount of aerosol produced by the electronic cigarette using this atomization component, thus impacting the inhalation experience. This is because an overly smooth heating element surface results in a weaker bond between the heating element and the ceramic layer. Firstly, the friction and interlocking force between the heating element with its smooth first surface and the second ceramic layer are low during demolding. Secondly, the difference in shrinkage forces between the heating element and the second ceramic layer during firing can lead to poor interfacial bonding between the metal heating element and the second ceramic layer, causing localized dry burning of the heating wire, which in turn affects the aerosol volume and inhalation experience.

[0159] The embodiments of the present invention have been described in detail above. However, the present invention is not limited to the above embodiments. Within the scope of knowledge possessed by those skilled in the art, various changes can be made without departing from the spirit of the present invention. Furthermore, the embodiments of the present invention and the features thereof can be combined with each other unless otherwise specified.

Claims

1. An atomizing component, characterized in that: The device includes a heating element and a first ceramic layer, a second ceramic layer, and a third ceramic layer stacked sequentially. The pore sizes of the first and third ceramic layers are both larger than those of the second ceramic layer, and the thermal conductivity of the first and third ceramic layers is also greater than that of the second ceramic layer. A gas channel is provided in the second ceramic layer. The heating element includes a first surface and a second surface disposed opposite to each other. The first surface is in contact with the second ceramic layer, and the second surface faces the gas channel. The roughness of the first surface is greater than that of the second surface. The pore sizes of the first and third ceramic layers are 11~20μm, respectively; the pore size of the second ceramic layer is 4μm~10μm. The thermal conductivity of the first ceramic layer and the third ceramic layer are 0.6~1.2 W / m·K, respectively; the thermal conductivity of the second ceramic layer is 0.3~0.6 W / m·K. The roughness Ra value of the first surface is greater than 1µm, and the Rz value is greater than 5µm; the roughness Ra value of the second surface is less than 0.2µm, and the Rz value is less than 1.4µm.

2. The atomizing component according to claim 1, characterized in that: The first ceramic layer and the third ceramic layer each have at least one of the following characteristics: (a) Thickness is 0.8~1.2mm; (b) By mass percentage, the raw materials for preparing the first ceramic layer and the third ceramic layer respectively include 45-70% ceramic powder A, 15-30% pore-forming agent, and 15-25% sintering aid; wherein the ceramic powder A is selected from at least one of alumina powder, silicon carbide powder, silicon nitride powder, and aluminum nitride powder.

3. The atomizing component according to claim 1, characterized in that: The second ceramic layer has at least one of the following characteristics: (a) Thickness is 3~5mm; (b) The second ceramic layer comprises the following raw materials by mass percentage: 35-60% ceramic powder B, 15-30% pore-forming agent, 17-35% sintering aid, 0.8%-1.5% release agent A, and 7%-10% green body reinforcing agent A; wherein the ceramic powder B is selected from at least one of silica powder, alumina powder, cordierite powder, and silicon nitride powder.

4. The atomizing component according to claim 2 or 3, characterized in that: The raw materials for preparing the second ceramic layer contain mold release agent A and green body reinforcing agent A; the raw materials for preparing the first ceramic layer and the third ceramic layer contain mold release agent B and green body reinforcing agent B, respectively; the mass ratio of mold release agent A to mold release agent B is (1.2~1.7):1; the mass ratio of green body reinforcing agent A to green body reinforcing agent B is (1.2~1.7):

1.

5. The method for preparing the atomizing component according to any one of claims 1 to 4, characterized in that: Includes the following steps: S1: Spread the raw materials for preparing the first ceramic layer evenly; S2: Spread part of the preparation material for the second ceramic layer on the surface of the preparation material for the first ceramic layer, place a metal mold with a heating element in it, and then spread the remaining preparation material for the second ceramic layer. S3: The raw material for preparing the third ceramic layer is laid flat on the surface of the raw material for preparing the second ceramic layer, and then pressed to obtain a ceramic green body; S4: The ceramic green body is dried and demolded, and then calcined to obtain the atomizing component.

6. The method for preparing the atomizing component according to claim 5, characterized in that: Step S4 is as follows: the ceramic green body is dried at 70~90℃ for 15~30min, then demolded with a draft angle of no more than 5°, dried again at 100~130℃ for 5~30min, and then calcined at 700~800℃ to obtain the product.

7. The method for preparing the atomizing component according to claim 5, characterized in that: Step S4 is as follows: the ceramic green body is dried at 70~90℃ for 15~30min, then demolded with a draft angle of no more than 5°, and then calcined at 700~800℃ to obtain the product.

8. An electronic atomizing device, characterized in that: Includes the atomizing component as described in any one of claims 1 to 4.

9. The application of the atomizing component according to any one of claims 1 to 4 in the field of electronic atomization.

Citation Information

Patent Citations

  • Composite ceramic part and preparation method thereof, atomization assembly and electronic cigarette

    CN112390625A

  • Composite ceramic member and method for preparation thereof, vaporization assembly, and electronic cigarette

    US20220281775A1